A bibliometric analysis of studies on the gut microbiota in cardiovascular disease from 2004 to 2022 - Sheng, Ming; Xu, Shuquan; Chen, Wei-wei; Li, Fa-quan; Zhong, Yi-ming; Ouyang, Yi-xiang; Liao, Yong-ling; Lai, Ping (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Background: Increasing evidence indicates that gut microbiota (GM) is linked to cardiovascular diseases (CVDs). Many studies on GM in CVDs have been published in the last decade. However, bibliometric analysis in this field is still lacking. Methods: On September 30, 2022, the Web of Science (WOS) yielded 1500 articles and reviews on GM in CVD. Microsoft Excel software, CiteSpace, and VOSviewer software were used to analyze publication trends and research hotspots in this field. Results: Our search generated 1,708 publications on GM in CVDs published between 2004 to 2022, and 1,500 articles and review papers were included in the final analysis. The publication on GM in CVD increased from 1 in 2004 to 350 in 2021. China (485 publications, 9,728 non-self citations, and H-index of 47) and the USA (418 publications, 24,918 non-self citations, and a H -index of 82) contributed 32.31%, and 27.85%, respectively, of the total publications. Regarding the number of publications (Np) and number of citations without self-citations (Nc) for authors. Y. L. Tian (Np: 18, Nc: 262, and H-index: 12) from China is the most productive author, followed by R. Knight (Np: 16, Nc: 3,036, and H-index: 15) and M. Nieuwdorp (Np: 16, Nc: 503, and H-index: 9). The Chinese Academy of Medical Sciences & Peking Union Medical College has the most publications (Np:62, Nc: 3,727, and H-index: 13, average citation number (ACN): 60.11). The journal Nutrients had the most publications (Np: 73, Nc: 2,036, and ACN: 27.89). "Monooxygenase 3" (strength 3.24, 2020–2022), "short-chain fatty acid" (strength 4.63, 2021-2022), "fatty liver disease" (strength 3.18, 2021-2022), "metabolic disease" (strength 3.04, 2021-2022), "Mediterranean diet" (strength 2.95, 2021-2022), Prevention (strength 2.77, 2021-2022), and "intestinal barrier" (strength 2.8, 2021-2022) were the emerging keywords in this field. Conclusion: Publications on GM in CVDs rapidly increased in the last decade. The USA was the most influential country in publications in this field, followed by China. The journal with the most publications was Nutrients. Monooxygenase-3, short-chain fatty acid, fatty liver disease, metabolic disease, the Mediterranean diet, intestinal barrier, and prevention are the current hotspot or potential hotspot in the future study.